INTEGRASI STEM DAN HOTS DALAM PEMBELAJARAN SAINS: PERSPEKTIF GURU DALAM UPAYA PENINGKATAN SELF EFFICACY SISWA - Putra, Erik Perdana; ., Zulkarnain; Walid, Ahmad (Program Studi Pendidikan IPA FKIP Universitas Jember, 2024)
Science, Technology, Engineering, and Mathematics (STEM) approach integrated with High Order Thinking Skills (HOTS) has been recognized as an innovative method in enhancing 21st century skills, including critical thinking, creativity, and collaboration. This study aims to explore science teachers' perceptions of STEM-HOTS implementation and its impact on improving students' self-efficacy in senior high schools in Bengkulu Province, Indonesia. This qualitative research used a survey method with semi-structured interviews with 13 science teachers from various public schools. The results showed that 77% of the teachers understood the concept of STEM, but none of them applied it in learning. The teachers realized the benefits of STEM in improving students' skills, but faced constraints such as lack of training, facilities and interdisciplinary collaboration. Nonetheless, teachers showed enthusiasm to implement this approach in the future. This study highlights the importance of continuous professional training, provision of resources and policy support to integrate STEM-HOTS in learning. The results of this study make an important contribution to the development of relevant learning strategies to improve the quality of education in Indonesia.